Study of Empowering The 5.0 Educator: A Path Analysis of Digital Leadership and Technological Self-Efficacy Toward Sustainable Educational Excellence - Hernawati W Retno Wiratih; Kasful Anwar; Risnita Risnita; Abdul Halim (Siber International Journal of Education Technology (SIJET), 2026)
This study investigates the psychological drivers of institutional transformation in the Society 5.0 era, specifically within the Indonesian educational landscape of 2022–2026. Titled "Empowering the 5.0 Educator," the research utilizes a Path Analysis framework via SEM-PLS to examine the impact of Digital Leadership, Technological Self-Efficacy, and a Human-Centric Learning Environment on Educational Sustainability. Central to this model is the mediating role of Innovative Work Behavior (IWB). Aligning with UNESCO Education 2030 (SDG 4) and the ASEAN Digital Masterplan 2025/2026, the study posits that technological integration alone is insufficient for excellence. Preliminary analysis suggests that while Digital Leadership and Self-Efficacy provide the necessary strategic and psychological foundations, their impact on long-term sustainability is fully realized only when they trigger the three stages of IWB: idea generation, promotion, and realization. Furthermore, a human-centric environment is found to be a critical prerequisite for mitigating technostress and ensuring resilient outcomes. The findings provide a strategic blueprint for educational management to move beyond automation toward a human-agentic ecosystem. Recommendations emphasize fostering digital advocacy and ethical AI governance to achieve inclusive, sustainable educational excellence in a rapidly evolving regional digital economy.